Rolling and pitching oscillating foil propulsion in ground effect. (27th November 2017) - Perkins, Matthew; Elles, Dane; Badlissi, George; Mivehchi, Amin; Dahl, Jason; Licht, Stephen
Abstract: In this paper, we investigate the effect of operating near a solid boundary on the forces produced by harmonically oscillating thrust-generating foils. A rolling and pitching foil was towed in a freshwater tank in a series of experiments with varying kinematics. Hydrodynamic forces and torques were measured in the freestream and at varying distances from a solid boundary, and changes in mean lift and thrust were found when the foil approached the boundary. The magnitude of this ground effect exhibited a strong nonlinear dependence on the distance between the foil and the boundary. Significant effects were found within three chord lengths of the boundary, and ground effect can be induced at greater distances from the boundary by biasing the tip of the foil toward the boundary. Lift coefficients changed by as much as 0.2 at the closest approach to the ground, with changes > 0.05 for all cases across Strouhal numbers ranging from 0.3 to 0.6, and nominal maximum angle of attack ranging from 20 ∘ to 40 ∘ . The ubiquity of the ground effect in high thrust kinematics suggests that the ground effect can provide a passive obstacle avoidance capability for foil propelled vehicles. By comparison with previous experimental work, we find that the ground effect experienced by a high-aspect ratio rolling and pitching foil is a fully three-dimensional phenomenon, as it is not accurately predicted when two-dimensional flow and/or two-dimensional kinematics are enforced. While two-dimensional foil kinematics are more easily modeled for numerical studies, three-dimensional foil kinematics may be more practical for real world implementation in underwater vehicles.